Forme indigene di simbiosi fra gruppi pigmei e gruppi sedentari in Africa equatoriale - Allovio, Stefano (L’Uomo Società tradizione sviluppo, 2022)
In Equatorial Africa, interactions between hunter-gatherer pygmies and their farmer neighbours (villagers) are very recurrent. Most of the recent anthropological research have been conducted with the assumption of standard categories of patron-client and valorisation of material and ecological data. Little attention has been paid to the symbolic and cultural dimensions of these relations. The author explore the ideas and beliefs underlying the foragers/farmer interaction in the northeastern Congo. Blood brotherhood (noutu) in mangbetu-asoa society and homonymy (atu) in lese-efe society are native representations of such relations.